2016
DOI: 10.1007/s00198-016-3632-5
|View full text |Cite
|
Sign up to set email alerts
|

Stroke increases the risk of hip fracture: a systematic review and meta-analysis

Abstract: Many studies have investigated the association between stroke and hip fracture risk, but the precise association was still unclear due to insufficient statistical power in single studies with relatively small sample size. Thus, we firstly conducted a meta-analysis of all published studies to precisely estimate the relationship of stroke with hip fracture risk. The strength for this relationship was weighed by pooled relative risks (RRs) with 95 % confidence intervals (95 % CIs) after adjustment for confounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 41 publications
2
17
1
1
Order By: Relevance
“…For more comprehensive lists of risk factors we refer to the literature [41]. Three German studies [42][43][44] support earlier findings [45][46][47] of an increased risk of hip fractures in people with Parkinson's disease, after stroke, or in patients with dementia.…”
Section: Risk Factorssupporting
confidence: 63%
“…For more comprehensive lists of risk factors we refer to the literature [41]. Three German studies [42][43][44] support earlier findings [45][46][47] of an increased risk of hip fractures in people with Parkinson's disease, after stroke, or in patients with dementia.…”
Section: Risk Factorssupporting
confidence: 63%
“…Both stroke and hip fracture are associated with significant disability, morbidity and mortality 6 29 56. People who suffered stroke are at much higher risk of developing hip fractures within 2 years following stroke, as compared with general population without stroke 11 57.…”
Section: Discussionmentioning
confidence: 99%
“…It contributes to disability, morbidity and mortality due to functional loss, and further imposes a considerable socioeconomic burden on society and contributes to deterioration in quality of life 3–5. Stroke is a major risk factor for hip fracture that increases the risk of hip fracture by two to four times 6 7. Jørgensen et al 8 reported that the bone mineral density decreased remarkably soon after stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(10) In a meta-analysis of 11 studies, the risk of hip fracture was increased after a stroke (relative risk [RR] ¼ 2.06, 95% CI 1.68 to 2.52). (11) Hip fracture is particularly common immediately after the stroke; in one study, the hazard ratio was 3.9 within 1 month and 1.5 in the first 5 years after stroke. (12) Recurrent falls (and the fear of falling) are more common after stroke.…”
Section: Parkinson's Diseasementioning
confidence: 98%